Over-expression of Escherichia coli transaldolase in the cytosol of Arabidopsis thaliana - Nulit, Rosimah (Universiti Putra Malaysia Press, 2012)
Transaldolase (TAL) is an enzyme of the oxidative pentose phosphate pathway (OPPP) which catalyzes the reversible reaction of sedoheptulose-7-phophate into fructose-6-phosphate and erythrose-4-phosphate. In some micro-organisms, fungi and plants, erythrose-4-phosphate condenses with phosphoenolpyruvate (PEP) from glycolysis to form chorismate which is a precursor for many secondary metabolic pathways such as aromatic amino acids, flavonoids, lignin, indole acetate and UV light protectants. An analysis of plant genome databases reveals that the OPPP is incomplete in the cytosol of plants as no genes encoding for a cytosolic transaldolase (TAL) and transketolase (TK) have been identified so far. Thus, this study attempted to complete the compartmentation of TAL in the cytosol and plastid of plants by over-expressing it in the cytosol of A. thaliana. For this purpose, homozygous transgenic plants were obtained in these studies; it was found that the transaldolase activity of transgenic lines increased as compared to wild type plants. The findings of the current study also demonstrated that transgenic plants did not show any distinct phenotypes and there was no difference in a range of growth parameters compared with A. thaliana Col-0 (wild type).